PRODUKSI GLUKOSA DARI BATANG KELAPA SAWIT MELALUI PROSES HIDROLISIS SECARA ENZIMATIS MENGGUNAKAN AMILASE TERMOSTABIL - Marlida, Yetti; -, Mirzah; Arief, Syukri; Amru, Khoirul (Jurnal Riset Kimia, 2014)
ABSTRACTThis study aimed to explore the optimization of the concentration of oil palm trunks andthermostable amylase enzyme preformance produce highest sugar (glucose total and reducingsugars) as well as the degree of polymerization. The design used in this study was a completelyrandomized design (CRD) factorial using 2 factors: factor A which consists of four levels ofamylase enzyme that A1: 250 units / kg, A2: 500 units / kg, A3: 750 units / kg and A4: 1000 units/ kg. Factor B is the concentration of oil palm trunk yitu B1: 20% (200 g / 1 liter) B2: 40% (400g / 1 liter) and B3: 60% (600 g / 1 liter) were repeated 3 times. The results showed that there is ahighly significant interaction (P <0.01) in the levels of amylase enzyme (factor A) with theconcentration of oil palm trunks (factor B) on reducing sugar, siqnificantly interaction (P <0.05)on total sugars and degree of polymerization (DP) . This research can be concluded that the besttreatment at a concentration of 60% oil palm trunks and levels 250 unit/kg of an enzymeconcentration that produces of total sugars 7.86 mg/ml, reducing sugar 15.69 mg /ml and degreeof polymerization 0.50Keywords : amilase, total gula, gula pereduksi, derajat polimerisasi.